TRANSFORMASI KEBUDAYAAN DALAM MASYARAKAT ILMIAH: TANTANGAN HUMANISME DI ERA DIGITAL - Gina Garnika Dwinita; Suzahra Salsabila; Jenuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The cultural transformation within the scientific community has accelerated significantly with the rise of digital technologies that reshape communication patterns, collaboration models, and knowledge production processes. These changes not only influence the structure and values of scientific culture but also introduce new challenges to the continuity of humanism, particularly regarding ethics, empathy, and moral responsibility within academic environments. Amid these dynamics, the relationship between science, technology, and humanism has become increasingly complex, as technological advancement often enhances rational efficiency while potentially marginalizing essential humanistic dimensions. Scientific progress strongly impacts culture and humanity by shaping how individuals think, act, and perceive social realities. However, such positive contributions may become problematic when scientific development is not balanced with ethical reflection and awareness of humanistic values. Therefore, maintaining equilibrium between scientific rationality and humanistic principles is crucial for the scientific community in the digital era to ensure that knowledge advancement remains aligned with human dignity and cultural sustainability